Adjusted Purchase Price as A Method of Valuing Financial Assets and Liabilities - Marek WIERZBIŃSKI; Zofia WIERZBIŃSKA (Communications of International Proceedings, 2024)
The development of accounting in modern times is accompanied by the emergence of new valuation methods. Today, assets and liabilities are disclosed not only in simple categories, such as purchase price, nominal value or production cost. National and international regulations introduce more complex valuation methods. One of them is the adjusted purchase price method, known in international regulations as the amortized cost method. The following article will present the essence of the adjusted purchase price method, the assets and liabilities that can be valued according to this method, as well as a comparison of the discussed valuation method with accounting principles.